Fluid power technology - Srivatsa, Ram S. (Standard Book House, 2009)
This fluid power text uses a balance of U.S. Customary and S.I. units. It begins with six basic hydraulic chapters, then discusses control valves, conduits and filtration, and ends with a solid overview of pneumatics. Includes strong problem sets and a detailed and precise art program. Six appendices include ISO viscosity grades, fluid power standards, ISO graphic symbols, and more.